Journal of Human Sport and Exercise - 2021 - Autumn Conferences of Sports Science 2021
DOI: 10.14198/jhse.2021.16.proc2.13
|View full text |Cite
|
Sign up to set email alerts
|

The positive impact of physical activity on working memory abilities: Evidence from a large Italian pre-adolescent sample

Abstract: Physical activity (PA) is an essential component of people's well-being. Copious evidence argues for its protective effect across individuals' lifespan. However, its role as a factor of enhancement for human cognitive skills is still a matter of study. The present work aims to provide conclusive evidence about PA's role in modulating working memory skills in active pre-adolescent children. By enrolling a large number of participants, we tested the effect of PA on Digit Span Backwards (DSB), a well-consolidated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Although of no practical importance, those MC differences should be considered for the training programs improvement in order to provide children with the necessary opportunities for the development of their MC. Regarding EFs, boys and girls presented similar scores; a finding that is in agreement with the study of Russo et al [23], in which the two genders had similar EFs scores. Furthermore, our results are supported by several meta-analyses, which provide evidence about the similar performance of boys and girls in EFs [74][75][76].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although of no practical importance, those MC differences should be considered for the training programs improvement in order to provide children with the necessary opportunities for the development of their MC. Regarding EFs, boys and girls presented similar scores; a finding that is in agreement with the study of Russo et al [23], in which the two genders had similar EFs scores. Furthermore, our results are supported by several meta-analyses, which provide evidence about the similar performance of boys and girls in EFs [74][75][76].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, our findings are in line with studies with children who participated in similar sports. Russo et al [23] identified a lack of differences in working memory between participants in open-(tennis, basket, football) and closed-skill sports (track and field, swimming, rhythmic gymnastics) in preadolescents. Furthermore, Formenti et al [12] were led to the same conclusion, comparing inhibitory control between participants in football, basketball, volleyball, and martial arts and those in swimming, rhythmic gymnastics, and ballet, where they only detected better accuracy in incongruent trials in favor of open-skill participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As can be appreciated from the results of this study, at the moment, it is still unclear what concrete effects this reform will have on the professional future of kinesiologists but more importantly on the effective health protection of citizens who participate in sports. Encouraging proper physical and sports practice in citizens of all ages is important given its benefits, especially in the wake of the COVID-19 pandemic [ 24 , 25 , 26 ]. In order to achieve maximum benefits, the technical-practical skills and expertise of the kinesiologist are crucial.…”
Section: Discussionmentioning
confidence: 99%